Recent Clinical Research on Glaucoma - Garcia-Medina, Jose Javier; Pinazo-Duran, Maria Dolores (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the past few years, knowledge about glaucoma diagnosis and follow up has evolved dramatically through advances in intraocular pressure (IOP) measurement, corneal biomechanics, structural and functional assessment of the ocular surface, anterior chamber, retina, optic nerve and intracranial visual pathways, as well as the advent of artificial intelligence. In addition, the development of new modalities of IOP-lowering and non-IOP-lowering drugs, alternative deliveries, refined laser technologies, and minimally invasive glaucoma surgery (MIGS) techniques with different implants have widened the therapeutic possibilities for treating this disease. Finally, current insights into risk factors and quality of life in relation to glaucomatous impairment are emerging. The purpose of this Special Issue is to present the latest exciting clinical developments that are taking place in the field of glaucoma.